2023
DOI: 10.1007/s00382-023-06931-3
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of near-surface wind speed from observational, reanalysis and high-resolution regional climate model data over the Tibetan Plateau

Lorenzo Minola,
Gangfeng Zhang,
Tinghai Ou
et al.

Abstract: As near-surface wind speed plays a role in regulating surface evaporation and thus the hydrological cycle, it is crucial to explore its spatio-temporal characteristics. However, in-situ measurements are scarce over the Tibetan Plateau, limiting the understanding of wind speed climate across this high-elevation region. This study explores the climatology of near-surface wind speed over the Tibetan Plateau by using for the first time homogenized observations together with reanalysis products and regional climate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…They concluded that the WRF model is capable of accurately analyzing significant weather phenomena on the Qinghai-Tibet Plateau. Chen et al [31], Minder et al [32], and Wrzesien et al [33] have all verified the feasibility of using the WRF model to simulate precipitation in a complex topography area, and many scholars have used the WRF model to calculate southwest China [34][35][36]. Therefore, the above studies have demonstrated that applying the WRF model to the southwest region has credibility and can partially compensate for the lack of meteorological data.…”
Section: Introductionmentioning
confidence: 93%
“…They concluded that the WRF model is capable of accurately analyzing significant weather phenomena on the Qinghai-Tibet Plateau. Chen et al [31], Minder et al [32], and Wrzesien et al [33] have all verified the feasibility of using the WRF model to simulate precipitation in a complex topography area, and many scholars have used the WRF model to calculate southwest China [34][35][36]. Therefore, the above studies have demonstrated that applying the WRF model to the southwest region has credibility and can partially compensate for the lack of meteorological data.…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies have found considerable disparities in SWS long-term changes across land and ocean during historical periods. Specifically, the observed SWS has shown a significant decreasing trend in the past 50 years over land (Wu et al 2018, Zhang et al 2019, Minola et al 2024, and this decreasing has slowed down or even it started to increase in the past 20 years (Zhang and Wang 2020, which is known as the SWS 'stilling' and 'recovery' phenomenon (Roderick et al 2007, Zeng et al 2019. However, recent studies show an increasing trend over ocean in the last 40 years (Zheng et al 2016, Young andRibal 2019).…”
Section: Introductionmentioning
confidence: 99%